The Development of Indonesian Language Teaching Materials for Beginner Level of Foreign Speakers with Local Content - Suwandy Tanwin; Rosliani Rosliani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research is motivated by the scarcity of Bahan Ajar Bahasa Indonesia Untuk Penutur Asing (BIPA), especially cultural-charged teaching materials. Therefore, the development of BIPA teaching materials is needed. The problems examined in this study are (1) how the process of developing BIPA teaching materials containing Batak culture for beginner-level foreign speakers, (2) how the final results of the development of BIPA-charged Batak culture materials for beginner-level foreign speakers, (3) how the materials are feasible BIPA teaching contains Batak culture for beginner-level foreign speakers. This research uses the Research and Development (R&D) approach which is carried out in five stages, namely: (1) preliminary survey, (2) initial prototype development, (3) product design, (4) product validation, (5) product revision and improvement. This study uses two data collection techniques, namely observation and interviews to obtain data on the needs of teaching material development and assessment of teaching material prototypes. The results of this study are as follows. First, the development of BIPA teaching materials with Batak culture for beginner-level foreign speakers is carried out in five stages, namely: (1) a preliminary survey with techniques for analyzing existing teaching materials, (2) initial prototype development, (3) product design, (4) product validation, and (5) product revision and improvement. Second, the prototype of teaching material is developed with three parts including (a) physical form, (b) book cover, (c) content / material content. Third, the evaluation from experts which includes the graphic aspect gets 89.29%. In the aspect of content/material obtained 78.57%. In the presentation aspect, it gets 83.33%. Aspects of language and readability, obtain 100.00%.